Contribution of personal and environmental factors on positive psychological functioning in adolescents. (19th June 2015) - Fadda, Daniela; Scalas, L. Francesca; Meleddu, Mauro
ABSTRACT: This study examined self‐esteem as mediator in the relations of personal (extraversion, neuroticism) and environmental (maternal, paternal, peer‐relationships) variables with domains of positive psychological functioning (PPF) in adolescence (Satisfaction with life, Mastery, Vigor, Social Interest, Social Cheerfulness). We compared one‐sided and multidimensional models using a sample of 1193 high school students (592 males and 601 females). We examined variations in adolescent PPF as a function of parenting styles via independent examination of maternal and paternal bonding. Results supported the multidimensional models, which indicated direct effects of personality traits, maternal care and peer relationships, as well as indirect effects, mediated by self‐esteem, of all predictors on most PPF dimensions. Overall, our study provided a broader picture of personal and environmental predictors on different dimensions of PPF, which supported the mediating role of self‐esteem and emphasized the importance of considering multidimensional models to characterize PPF in adolescents.